Accumulation in East Greenland Fjords and on the Continental Shelves Adjacent to the Denmark Strait over the Last Century Based on 210Pb Geochronology - Smith, L. Micaela; Alexander, Clark; Jennings, Anne E. (ARCTIC, 2002)
Sediment (SAR) and mass (MAR) accumulation rates for the last 100 years are derived from 210Pb profiles of box cores collected in three fjords and on the continental shelf in the Kangerlussuaq region, East Greenland, and on the SW Iceland continental shelf. The MAR is lower on East Greenland (0.09 g/cm²·yr) than on SW Iceland (0.14 g/cm²·yr) because of differences in the biogenic component of the sediments, although SAR is similar. The differences in accumulation rates of the three East Greenland fjords are due to their dominant sediment sources and basin areas. Kangerlussuaq Fjord, the largest fjord, is dominated by iceberg sediment input and has a MAR of 0.43 g/cm²·yr at 50 km from the fjord head. Miki Fjord, the smallest fjord, is dominated by glaciofluvial sediment input with a MAR of 0.29 g/cm²·yr of sediment at 10 km from the fjord head. Nansen Fjord is intermediate in size, with an iceberg-dominated sediment supply; MAR is 1.01 g/cm²·yr near the fjord head and 0.17 g/cm²·yr at 20 km from the fjord head. 137Cs is used as a secondary indicator of sediment source, and the high activity level of 137Cs in Miki Fjord indicates glaciofluvial sediment sources. Zones of constant activity in some of the box cores are attributed to either bioturbation in the surface mixed layer or turbidites. We would be hesitant to extend the recent 210Pb-based accumulation rates to estimate the Holocene accumulation rates. On a calculé les taux d'accumulation de sédiments (TAS) et de masse (TAM) pour les cent dernières années à partir des profils du 210Pb dans des carottes rectangulaires prélevées dans trois fjords et sur le plateau continental de la région de Kangerlussuaq (est du Groenland), et sur le plateau continental du sud-ouest de l'Islande. Le TAM est plus faible dans l'est du Groenland (0,09 g/cm² par an) que dans le sud-ouest de l'Islande (0,14 g/cm² par an) en raison des différences dans la composante biogène des sédiments, bien que le TAS soit similaire. La différence entre les taux d'accumulation des trois fjords ...